Learning through VR gaming with virtual pink dolphins for children with ASD - Lu, Andrew (2019)
Autism Spectrum Disorder (ASD) is a developmental disorder with different levels of severity. Although the exact causes of ASD is not yet known, nor is there a medical cure for ASD to date, special facilities and schools have been established to help individuals coping better and becoming more independent. With the advancement in Virtual Reality (VR) technology, there has been a greater depth of development of technology-enhanced game-based learning for children with ASD. This paper will describe our effort on virtual pink dolphins to assist children with ASD in their learning, at the same time, to avoid the use of physical pink dolphins which is a species endangered. A study on the use of a low-cost VR enabled pink dolphins game for children with ASD to learn direction following, psychomotor skills and hand-eye coordination will be reported.